Tenocyte proliferation on collagen scaffolds protects against degradation and improves scaffold properties. - Tilley, J; Chaudhury, S; Hakimi, O; Carr, A; Czernuszka, J (2012)
Tissue engineering scaffolds encourage cell proliferation whilst degrading to facilitate tissue regeneration. Their mechanical properties therefore change, decreasing due to scaffold degradation and increasing due to extracellular matrix deposition. This work compares the changing properties of collagen scaffolds incubated in culture medium, with and without human tenocytes, in order to investigate the relationship between degradation and tenocyte proliferation. The material properties of scaffolds are compared over 26 days using mechanical testing, differential scanning calorimetry, infra-red spectroscopy, and histology and biochemical assays. For medium-only scaffolds, the mechanical properties decrease rapidly, while culture medium sulfhydryl content increases significantly, with no significant changes in the denaturation temperature of scaffold collagen content. Conversely, the mechanical properties and collagen content of tenocyte-seeded scaffolds increase significantly while culture medium sulfhydryl content decreases and denaturation temperature remains the same. These results indicate that tenocytes proliferation both reduces the degradation of collagen scaffolds incubated in culture medium and produces scaffolds with improved properties.